IS WHAT WE KNOW ABOUT POSTERIOR REVERSIBLE ENCEPHALOPATHY SYNDROME (PRES) TRUE? - Özlem Karabay Akgül; Erhan Okuyan; Evrim Ebru Kovalak; Güzide Ece Akıncı; Mehmet Salih Sevdi; Hakan Güraslan; Nurşen Kurtoğlu Aksoy; Neşe Hayıroğlu (Sabiad)
Objective: The aim of this study is to evaluate the risk factors and clinical course in cases of posterior reversible encephalopathy syndrome (PRES). Material and Methods: In this study, we retrospectively reviewed the data of pregnant or puerperal women diagnosed with PRES in the tertiary center emergency obstetrics outpatient clinic and intensive care unit between 2017 and 2022. All patients were evaluated by obstetrics, neurology, ophthalmology, radiology, and intensive care physicians, and blood tests and imaging were performed in the same center. Application complaints, laboratory values, imaging methods, comorbidities, mode of delivery, and postpartum period were evaluated for each patient. Results: In five years, a total of seven patients were diagnosed with PRES based on imaging methods and clinical findings. One of these patients had PRES twice, three years apart. Six of them presented with eclampsia. One patient was diagnosed with PRES postpartum in the first week, while other patients were diagnosed at pregnancy. Four patients had blurred vision, two patients had blindness, and one patient had no visual complaints. Three of the patients had mood changes (one patient confused, two patients agitated). One of the patients had diabetes mellitus (DM), which was known and treated with oral antidiabetics. One patient was under follow-up and treatment because of hypertension (HT) that started before pregnancy and three patients were under follow-up due to hypertension that started during pregnancy. There was no known additional disease in one patient. The delivery week of the patients was between 28 and 34 weeks of gestation. Pathological laboratory values were most frequently seen in LDH, albumin, and protein values. Every patient was discharged with outpatient follow-up. Epilepsy continues in one patient, HT in two patients, and isolated nephropathy in one patient after PRES. Conclusion: PRES should be considered especially in pregnant women with neurological symptoms including visual impairment and headache. Clinical suspicion and neuroimaging are required for the diagnosis of PRES.